Production and Inventory Management with Substitutions - Lang, J. Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book addresses production and inventory management problems where products can be replaced by specified substitutes. Depending on the considered application, substitutions can potentially improve the service level, reduce required safety stocks and total setup costs and times, utilize cost variations of input products, and reduce the amount of wastage. The main focus is the development of graphical modeling approaches for substitution options and of production planning models based on these approaches using mathematical programming. In addition to single-level dynamic lot-sizing models with substitutions, models for multi-level production systems with flexible bills-of-materials and recipes are devised. Also, a simulation-based optimization approach for a multi-location inventory system with substitutions is developed.
Production and Operations Management: Models and Algorithms -- Graphical Modeling of Substitutions and Flexible Bills-of-Materials -- Literature Review -- Efficient Reformulations for Uncapacitated and Capacitated Lot-Sizing with Substitutions and Initial Inventories -- MIP-Based Heuristics for Capacitated Lot-Sizing with Sequence-Dependent Setups and Substitutions -- Multi-Level Lot-Sizing Models with Flexible Bills-of-Materials -- Blood Bank Inventory Control with Transshipments and Substitutions -- Conclusions and Future Research.
Keywords: Economics; Operations research; Business logistics; Economics/Management Science; Production/Logistics.; Operations Research/Decision Theory; Operations Research, Mathematical Programming